Active-region twist derived from magnetic tongues and linear force-free extrapolations - Poisson, Mariano (2015)
The main aim of this study is to compare the amount of twist present in emerging active regions (ARs) from photospheric and coronal data. We use linear force-free field models of the observed coronal structure of ARs to determine the global twist. The coronal twist is derived, on one hand, from the force-free parameter [α] of the model and, on the other, from the computed coronal magnetic helicity normalized by the magnetic flux squared. We compare our results, for the same set of ARs, with those of Poisson et al. (Solar Phys. 290, 727, 2015), in which the twist was estimated using the so-called magnetic tongues observed in line-of-sight magnetograms during AR emergence. We corroborate the agreement between the photospheric and coronal twist-sign and the presence of magnetic tongues as an early proxy of the AR non-potentiality. We find a globally linear relationship between the coronal twist and the one previously deduced for the emerging AR flux rope at the photospheric level. The coronal-twist value is typically lower by a factor of six than the one deduced for the emerging flux rope. We interpret this result as due to the partial emergence of the flux rope that forms the region.